2020
DOI: 10.1302/0301-620x.102b6.bjj-2020-0195.r1
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the role of bladder scanning and post-void residual volume measurement in improving diagnostic accuracy of cauda equina syndrome

Abstract: Aims Diagnosis of cauda equina syndrome (CES) remains difficult; clinical assessment has low accuracy in reliably predicting MRI compression of the cauda equina (CE). This prospective study tests the usefulness of ultrasound bladder scans as an adjunct for diagnosing CES. Methods A total of 260 patients with suspected CES were referred to a tertiary spinal unit over a 16-month period. All were assessed by Board-eligible spinal surgeons and had transabdominal ultrasound bladder scans for pre- and post-voiding r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…they could void and were therefore CESI, we found 13 cases where the PVR was less than 200 ml, and the diagnosis was confirmed on MRI. Our patients are not exactly the same as the patients reported by Katzouraki et al 7 . Case 12 had bladder symptoms but normal perineal sensation and anal tone with a positive MRI.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…they could void and were therefore CESI, we found 13 cases where the PVR was less than 200 ml, and the diagnosis was confirmed on MRI. Our patients are not exactly the same as the patients reported by Katzouraki et al 7 . Case 12 had bladder symptoms but normal perineal sensation and anal tone with a positive MRI.…”
Section: Discussionsupporting
confidence: 52%
“…Worryingly, in our medicolegal practice, we are increasingly seeing doctors say that, because the symptoms and signs of CES are not diagnostic and because the PVR is a quantitative measurement, a PVR ≤ 200 ml indicates that the patient does not have CES even in the presence of objective signs. If it was thought that a PVR ≤ 200 ml did not require an MRI (which is not what Katzouraki et al 7 recommended), all 13 of our cases would have been missed. We believe that in some centres, PVR is being used in an uncritical way.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…More recently, from the same institute in 2020, Katzouraki et al followed 260 patients and found a similar predictive value of 200 ml with CE compression on MRI, and where candidates underwent subsequent surgery (P<0.0001, Fisher's exact test). The PVR volume >200 ml had a sensitivity of 94% in predicting CES and specificity 66.8%, with 29.9% positive predictive value and 98.7% negative predictive value [14].…”
Section: Reviewmentioning
confidence: 96%